The Implementation of Differentiated Instruction in English Classroom at Junior High School Level - Amrina; Wahyuni, Sri (Universitas Negeri Semarang, 2025)
This study aims to examine the implementation of Differentiated Instruction in English classrooms at SMP Negeri 14 Pekalongan and students' perceptions of the implementation of differentiated Instruction. The researcher employed a qualitative method. This research involved a class of 8 grade, 21 students, and an English teacher at SMP Negeri 14 Pekalongan during the academic year 2022/2023. This data was obtained using observation sheets, interviews, and questionnaires. The research findings show that Differentiated Instruction's approach involves adjusting content, processes, and products to cater to diverse learning preferences, leading to better academic performance and language acquisition. Positive student perceptions of DI indicate its success, with most students feeling they study consistent material and align with lesson plans. However, there is a need for improved support systems to ensure all students feel adequately supported. Thus, this research further examines the development, implementation, and evaluation steps, although differentiated learning is implemented in English classes.